Design and experiment of a high-clearance self-propelled sprayer chassis - Chen, Yu; Mao, Enrong; Li, Wei; Zhang, Shuo; Song, Zhenghe; Yang, Shanju; Chen, Jun (International Journal of Agricultural and Biological Engineering, 2020)
A large high-clearance self-propelled sprayer chassis was designed according to the requirements of the sprayer’s driving operation and the overall goal. The structural characteristics and working principle of the chassis drive system, suspension system, track adjustment system, and frame were analyzed. A finite element analysis of the frame was carried out under four extreme conditions: full load bending, full load torsion, full load emergency braking and full load emergency turning. Under these four conditions, the maximum stress values of the frame were 149.45 MPa, 219 MPa, 151.44 MPa, and 123.27 MPa respectively, and the maximum strain values were 1.12 mm, 2.22 mm, 0.95 mm, and 1.16 mm respectively. A theoretical analysis of the stability, steering ability, and obstacle navigation of the sprayer chassis was conducted. The results showed that the upper angle θlim, lower angle θ׳lim and lateral limit tumbling angle φlim of the sprayer chassis were 50.1°, 30.0° and 35.3° respectively. The minimum turning radius of the chassis was 5816 mm, and the minimum turning width was 4113 mm. The maximum obstacle crossing heights of the front and rear wheels were 466 mm and 457 mm. The theoretical analysis showed that the designed chassis met the field management operations of large plots. A field experiment of the high-clearance self-propelled sprayer chassis at full load was conducted. The experimental results were consistent with the theoretical analysis results. The sprayer chassis not only good handling stability but also good ride comfort. The results of this study provide references for the design of high-clearance self-propelled sprayer chassis.Keywords: high-clearance self-propelled sprayer, chassis performance, frame, suspension, design, experimentDOI: 10.25165/j.ijabe.20201302.5262Citation: Chen Y, Mao E R, Li W, Zhang S, Song Z H, Yang S J, et al. Design and experiment of a high-clearance self-propelled sprayer chassis. Int J Agric & Biol Eng, 2020; 13(2): 71–80.